Peningkatan Kreativitas dan Pemberdayaan Ekonomi Lokal Wanita Agen Pancasila Melalui Pelatihan Shibori Desa Bono - Aliyah, Sonia Darojatul; Shinta Nur Avivah; Moh. Hasan Bisri (Universitas Negeri Semarang, 2025)
Bono Village, located in Tulung District, Klaten Regency, Central Java, has great potential for local economic development through shibori training. The aim of the shibori making training is to provide experience to PKK women as women agents of Pancasila so that they can be used to help the village community's economy. This shibori program has important value because it focuses on empowerment through skill development. The method used in making shibori is done using a training method. The research results show that the importance of the role of women as Pancasila agents in the public sphere is related to how women carry out their social life, such as in the context of work, business, PKK activities, posyandu activities, social gatherings, recital studies and other social activities. The PKK women were very enthusiastic about implementing shibori. The pattern on the fabric produced corresponds to the result of the binding or folding carried out during the shibori making process. Activity evaluation shows that the ties in the Shibori technique must be done with precision so that they are not too loose or too tight. Techniques such as itajime (triangle), itajime (square), swirl, kumo, kanoko, and twist each have their own challenges in terms of tying and folding the fabric.